The Prairie and Deliverance: A Futile Search for a “Paradise Regained” - Djuhertati Imam Muhni (Faculty of Cultural Sciences, Universitas Gadjah Mada, 1998)
Through the fall of Adam and Eve, paradise was lost to human beings; the striving for its recovery never ends. The dream for a